Clinical and electrophysiological features of acute flaccid myelitis: A national cohort study. Issue 10 (October 2021) - Chong, Pin Fee; Torisu, Hiroyuki; Yasumoto, Sawa; Okumura, Akihisa; Mori, Harushi; Sato, Tatsuharu; Kimura, Jun; Ohga, Shouichi; Tanaka-Taya, Keiko; Kira, Ryutaro; ,
Highlights: Neurophysiological studies of acute flaccid myelitis show neuronopathic changes. Compound muscle action potential amplitude reflects disease severity of paralytic limbs and correlates with neuroimaging findings. Baseline manual muscle strength test grades and localized anterior horn lesions on neuroimaging predict motor outcome. Abstract: Objective: To summarize the neurophysiological properties of acute flaccid myelitis (AFM) and evaluate limb-based motor outcomes. Methods: Nerve conduction studies (NCS) in 49 patients (21 females, 28 males; median age = 52 m) with AFM (median = 7 d after onset; range 1–122 d) were reviewed. Neurophysiological findings, together with treatment and prognosis, and neurophysiology–neuroimaging correlations were analyzed. Results: The findings indicated that 64% of paralytic limbs during the acute stage (≤14 d after onset) showed diminished or absent compound muscle action potentials (CMAPs), 79% showed normal motor nerve conduction velocities, 55% showed decreased persistence or absent F-waves, and 95% showed normal sensory nerve conduction velocities. The rate of CMAP abnormalities increased from 41% on days 1–2 to 83% on days 13–14. The reduction in CMAP amplitude was correlated with weaker muscle strength at both the peak neurological deficit and the last follow-up. The baseline limb-based muscle strength at nadir and anterior horn-localized magnetic resonance imaging lesions at recovery stage (>14 d) were strong predictors of outcome at the last follow-up. Conclusions: AFM typically shows neurophysiological features of neuronopathy. Significance: NCS is probably useful in the diagnosis and evaluation of AFM.